Colon Capsule Endoscopy: Detection of Colonic Polyps Compared with Conventional Colonoscopy and Visualization of Extracolonic Pathologies - Alexander F Hagel; Erwin Gäbele; Martin Raithel; Wolfgang H Hagel; Heinz Albrecht; Thomas M de Rossi; Christine Singer; Thomas Schneider; Markus F Neurath; Michael J Farnbacher (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Conventional colonoscopy (CC) is the gold standard for diagnostic examination of the colon. However, the overall acceptance of this procedure is low due to patient fears of complications or embarrassment. Colon capsule endoscopy (CCE) represents a minimally invasive, patient-friendly procedure that offers complete visualization of the entire intestine.